THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, INTELLECTUAL CAPITAL, AND WORK ENVIRONMENT ON THE PERFORMANCE OF BAWASLU EMPLOYEES OF PASURUAN REGENCY - Mokhamad Alfian Fahmi; Eva Mufidah; M. Tahajjudi Ghifary (Universitas Islam Lamongan, 2023)
BAWASLU Pasuruan Regency is an institution that monitors election implementation, handles complaints, and overcomes administrative violations, election crimes, and ethics. This study analyzes the effect of Transformational Leadership, Intellectual Capital, and Work Environment on the performance of Bawaslu Employees. In a sample of 40 respondents, the quantitative approach involves Instrument Test, Classical Assumption Test, Multiple Linear Regression, and Hypothesis Test. The results show that Transformational Leadership, Intellectual Capital, and Work Environment have a significant impact on the performance of Bawaslu employees. Transformational Leadership and Intellectual Capital have a significant effect, while the Work Environment also has an effect with a significance value lower than the threshold of 0.05. These findings reinforce the role of these factors in improving the performance of Pasuruan Regency Bawaslu employees.